THE ROLE OF VILLAGE-OWNED ENTERPRISE AND WASTE BANKS IN VILLAGE DEVELOPMENT ( A STUDY IN VILLAGES IN CENTRAL SULAWESI PROVINCE) - Hartoyo, Rasyid Muhammad; Furqan, Andi Chairil; Erwinsyah; Utari, Andiani Purwa (Riau International Conference on Economics, Business and Accounting, 2024)
Village development in Central Sulawesi has become the main focus of the government and society in recent years. In an effort to improve the quality of life of village residents and preserve the environment, two concepts that are increasingly being accepted are Village-Owned Enterprises (BUMDES) and Waste Banks. This research aims to investigate the role of BUMDES and Waste Banks in village development efforts in the Central Sulawesi region. BUMDES is a business entity owned by village communities and run to advance community welfare. They have the potential to improve the village economy by driving local business sectors, such as agriculture, tourism and crafts. This research reviews the role of BUMDES in creating jobs, empowering village communities, and contributing to the development of social infrastructure. Waste Bank is a concept that aims to manage waste in a sustainable way. By collecting, recycling and selling waste, the Waste Bank helps reduce environmental pollution and increase people's income. This research discusses the role of Waste Banks in maintaining environmental cleanliness, supporting environmental education, and generating additional income for village communities. The results of this research provide insight into the extent to which BUMDES and Waste Banks can contribute to village development in Central Sulawesi. These findings can be a basis for developing more effective strategies in exploiting the economic and environmental potential that exists at the village level. By understanding this key role, villages in Central Sulawesi have a greater opportunity to achieve equitable and sustainable development.